The Influence of Work Environment on Employees Performance at the BPBD East Kalimantan Provincial - Destiana Pristi Wulandari; Muhammad Arif Nurrahman (Universitas Negeri Gorontalo, 2025)
This study aims to determine and analyze the effect of the work environment on employee performance at the Badan Penanggulangan Bencana Daerah (BPBD) East Kalimantan Provincial. This study was motivated by the low fulfillment of training hour standards, which indicates a gap in individual capacity development, as well as stagnant employee performance, which reflects the existence of inhibiting factors such as the work environment. This study uses a quantitative method with a causal associative approach to measure the influence of independent variables on dependent variables. The research sample included all employees of the BPBD East Kalimantan Province. The results of the study show that the work environment has a positive and significant effect on employee performance. The better the work environment, the higher the performance. These findings emphasize the importance of creating a comfortable and safe work environment as a strategy for improving performance in carrying out tasks, especially in the BPBD East Kalimantan Provincial.